Representações do feminino no cinema: uma análise semiológico-psicanalítica de filmes De Lars Von Trier - Miras, Elisangela (2013)
This research has as main proposal to make an analysis of the representation of women in films by Lars Von Trier. After a more close glance on Dancer in the Dark, Dogville and Melancholy, a corpus that covers the period from 2000 to 2011, I sought to indicate the strategies of meaning construction that interact here. Theoretically, this work requires the support of Barthes semiology, notably his classical concept of myth , as well as the Freudian-Lacanian psychoanalysis around women and female questions. The first one is a base for film analysis. The second helps me to analyse female characters. I added to these supports contributions of excellent thinkers about Freud and Lacan works, and also contributions of film scholars and analysers of Lars Von Trier masterpieces. Consistent with these perspectives, I launched here the following hypothesis: in the figuration of the feminine, nothing is linked to the so-called nature , rather to a historical and discursive construction. The relevance of the work is related to the almost total absence of Barthesian readings in the cientific Brazilian literature, specifically on films, and also to the rarity of media semiological and psychoanalytic approaches related to Barthes studies